Optimasi Formula Tablet Lepas Lambat Mucoadhesive Nifedipin dengan Carbopol 940 dan HPMC K15M Sebagai Matriks secara Simplex Lattice Design - Octavia Krisma O; T. N. Saifullah Sulaiman; Ilham Kuncahyo (Fakultas Farmasi Universitas Setia Budi, 2015)
Nifedipin is a calcium chanel blocker has been used for hypertension treatment. Nifedipin has a short half-life (2-4 hours), and perfectly absorb in stomach. These characteristics indicate a good candidate for mucoadhesive formulation. This research aimed to optimize and determine the influence of the Carbopol 940 and HPMC K15M proportion on the physical properties of the tablet and the drug release. Tablets preparation using dry granulation method was carried out using difference proportion of HPMC K15M (A) and Carbopol 940 (B) for each formula i.e. 0% A: 100% B 940, 25% A: 75% B, 50% A: 50% B, 75% A: 25% B and 100% A: 0% B. The weighting of each tablet 250 mg with nifedipin 20 mg per tablet. Mucoadhesive strength was determined using rabbit gastric and the drug release using buffer chloride addition by 0.5% sodium lauryl sulfate pH 1.2 for 6 hours. Optimum formula was analyzed using simplex lattice design method. The results showed that increasing proportion of Carbopol 940 increased the tablet hardness and mucoadhesive strength and increasing the proportion of HPMC K15M reduced the drug release. Optimum formula was obtained at proportion of HPMC K15M 30,610 mg and Carbopol 940 mg 19,390 mgKeywords : Nifedipin, mucoadhesive, HPMC K15M, Carbopol 940.